The Effect of Education with Booklet Media on Pregnant Women's Nutrition Knowledge in Stunting Prevention Efforts - Dewi Mulfiyanti; Andi Satriana; Fitrah Ramadani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Stunting (short) or failure to grow is a condition that describes the undernutrition status that has a chronic nature during the growth and development of children from the beginning of life. Pregnant women who experience nutritional deficiencies can have an impact on stunting. Therefore, it is necessary to prevent stunting, one of the ways to prevent it with education to increase pregnant women's knowledge about nutrition. Education is obtained from various media, one of which is a booklet. Objective: The purpose of this study is to determine the influence of educational booklet media about nutrition in pregnant women on maternal knowledge in the working area of the Ajangale Health Center. Method: The research design uses Quasi Experiment with a pre-test post test one group design. The sample used was 30 respondents with purposive sampling techniques. This research tool uses nutrition knowledge questionnaires and booklets. In this research, researchers used quantitative data analysis, namely consisting of univariate analysis and bivariate analysis.In this study, univariate analysis was used to determine maternal knowledge about nutrition in pregnant women to prevent stunting. Nutritional knowledge in pregnant women before the intervention using booklet media and nutritional knowledge in mothers after the intervention using booklet media.Results: The results of the study showed that before the knowledge education was carried out, the majority of respondents were in the sufficient category with an average score of 13.90 and after the knowledge education was carried out the majority of respondents were good with an average score of 19.32. The Wilcoxon test obtained a p-value of 0.023 which means that there is an effect of providing health education about nutrition in pregnant women Conclusions The booklet media can be an educational medium to increase the knowledge of pregnant women about nutritional needs during pregnancy.